In vitro characterization of 3D culture-based differentiation of human liver stem cells - Tapparo, Marta; Saccu, Gabriele; Pasquino, Chiara; Fonsato, Valentina; Medana, Claudio; Schiavo, Valentina; Mecarelli, Enrica; Maccagno, Monica; Silengo, Lorenzo; Bruno, Stefania; Camussi, Giovanni; Herrera Sanchez, Maria Beatriz (Frontiers in Cell and Developmental Biology, 2024)
The lack of functional hepatocytes poses a significant challenge for drug safety testing and therapeutic applications due to the inability of mature hepatocytes to expand and their tendency to lose functionality in vitro. Previous studies have demonstrated the potential of Human Liver Stem Cells (HLSCs) to differentiate into hepatocyte-like cells within an in vitro rotary cell culture system, guided by a combination of growth factors and molecules known to regulate hepatocyte maturation.In this study, we employed a matrix multi-assay approach to comprehensively characterize HLSC differentiation. We evaluated the expression of hepatic markers using qRT-PCR, immunofluorescence, and western blot analysis. Additionally, we measured urea and FVIII secretion into the supernatant and developed an updated indocyanine green in vitro assay to assess hepatocyte functionality. Molecular analyses of differentiated HLSC aggregates revealed significant upregulation of hepatic genes, including CYP450, urea cycle enzymes, and uptake transporters exclusively expressed on the sinusoidal side of mature hepatocytes, evident as early as one day postdifferentiation. Interestingly, HLSCs transiently upregulated stem cell markers during differentiation, followed by downregulation after 7 days. Furthermore, differentiated aggregates demonstrated the ability to release urea and FVIII into the supernatant as early as the first 24 hours, with accumulation over time. These findings suggest that a 3D rotation culture system may facilitate rapid hepatic differentiation of HLSCs. Despite the limitations of this rotary culture system, its unique advantages hold promise for characterizing HLSC GMP batches for clinical applications.